2022
DOI: 10.1371/journal.pone.0267276
|View full text |Cite
|
Sign up to set email alerts
|

The remarkable genetic relationship between Staphylococcus aureus isolates from hemodialysis patients and their household contacts: Homes as an important source of colonization and dissemination

Abstract: Introduction Staphylococcus aureus is a successful pathogen in hospital and community. Hemodialysis patients have high colonization rates. Interactions between them and their household contacts, are an opportunity to understand the S. aureus colonization between hospitals and community. This study aims to determine the clinical and epidemiological characteristics of S. aureus colonization in hemodialysis patients and their household contacts, as well as the genetic relationship between their isolates. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Due to close contact, dogs and cats were colonized or infected with MRSA by humans, according to molecular typing [ 59 ]. Colonial complexes (CCs) of MRSA in dogs and cats include MRSA CC22, CC8, CC239, CC5, and CC59 [ 59 ], while in exotic animals, several MRSA colonic complexes have been detected, including MRSA CC8 and CC22 [ 60 ].…”
Section: Molecular Typing Of Mrsa In Pet Animalsmentioning
confidence: 99%
“…Due to close contact, dogs and cats were colonized or infected with MRSA by humans, according to molecular typing [ 59 ]. Colonial complexes (CCs) of MRSA in dogs and cats include MRSA CC22, CC8, CC239, CC5, and CC59 [ 59 ], while in exotic animals, several MRSA colonic complexes have been detected, including MRSA CC8 and CC22 [ 60 ].…”
Section: Molecular Typing Of Mrsa In Pet Animalsmentioning
confidence: 99%
“…A systematic review showed a transmission risk of ±40% within households [ 3 ], indicating that close contacts may serve as an external reservoir for S. aureus (re)colonization and infection. Many studies used non–whole-genome sequencing (non-WGS) based genotyping to confirm that people of the same household carry genetically related S. aureus strains [ 3 , 4 ]. These methods lack resolution to confirm transmission between patients and their close contacts.…”
mentioning
confidence: 99%